A flowing culture: Images of early Gujarati Indian-Islamic migrants in Aotearoa New Zealand. Issue 2 (1st October 2017) - Patel, Rafik
Salman Rushdie's Haroun and the Sea of Stories (1990) sets up an imaginative tale of a father and son's journey in search of happiness. In this fictional reality the ocean is filled with a sea of stories that manifest the hope of a new beginning. This story also takes the reader on a whimsical journey that is non-linear. It sways back and forth like the currents of the ocean, and its allegory transcends the ocean as a vessel that contains important narratives and knowledge, and as a spatial medium to cross borders and boundaries. Considering this allegory, this article presents an auto-ethnography in relation to migration of the first Gujarati Indian families to arrive in Aotearoa New Zealand, in the early 1900s. It discusses how these families integrated and began to construct and grow a new community within. Thus, this article attempts to uncover stories and a history of migration of the author's own family that flowed from South Asia to the Pacific, transferring a rich culture of Indian-Muslim faith, practice and architecture.